Validation of the Polish version of the DREEM questionnaire – a confirmatory factor analysis - Dorota Wójcik; Leszek Szalewski; Adam Bęben; Iwona Ordyniec-Kwaśnica; Sue Roff (BMC Medical Education, 2023)
Abstract Aim The aim of our study was to translate and adapt the Dundee Ready Education Environment Measure (DREEM) questionnaire developed by Roff et al. to the cultural conditions in Poland and also to validate it. Studying the learning environment is beneficial because it can identify students’ perceptions of their environment and support the staff in reflecting on, planning for and combining proper teaching approaches to improve it. Methods The DREEM questionnaire was completed by students of all years (first–fifth) in the faculties of dental medicine at the Medical University of Lublin and the Medical University of Gdańsk. The total surveyed population consisted of 650 students. Validity was separated into four phases: (1) translation validity, (2) confirmatory factor analysis, (3) concurrent validity and (4) criterion-related validity. Results Our study confirmed the original structure of the DREEM tool (GFI = 0.955, AGFI = 0.951, NFI = 0.931, TLI = 0.962, CFI = 0.964, RNI = 0.964, IFI = 0.964, RFI = 0.928, PNFI = 0.885, SRMR = 0.062, RMSEA = 0.043, 90% CI = 0.041–0.046) and obtained very good reliability rates, with Cronbach’s alpha > 0.7 for all scales. Only Subscale V achieved a lower Cronbach’s alpha of > 0.5. The study was conducted using the test–retest method, which is why the intraclass correlation coefficients for reliability were also calculated; individual items showed both medium and good correspondence. Conclusions Our study provided good evidence for the reliability and validity of the Polish version of the DREEM. In conclusion, the Polish-language version of the DREEM questionnaire is a reliable and valid instrument for analysing the learning environment for dental students and its factor structure is supported by the data.